Marine Arthrobacter enclensis NIO-1008T as a salicylic acid producing biocontrol agent against Fusarium oxysporum - Kharat, Bharat A.; Said, Madhukar S.; Dastager, Syed G. (European Journal of Plant Pathology, 2026)
The importance of microorganisms in plant growth promotion (PGP) and disease control has long been acknowledged. However, marine bacteria have been largely neglected in agricultural applications. In this study, previously identified marine strain Arthrobacter enclensis NIO-1008T has been explored for mitigation of Fusarium oxysporum NCIM 1281 infestation on wheat plants. A genome analysis study confirmed strain NIO-1008T has protein encoding genes associated with stress tolerance, antifungal activity and PGP. A growth attributes study showed strain NIO-1008T has the ability to grow at 4-11 pH, 6% NaCl and in presence of heavy metals. PGP traits, such as ammonia, siderophore and total indole (640 +/- 9 mu g/mL), were also confirmed. Moreover, an antagonistic assay showed 66 +/- 2% F. oxysporum mycelial growth inhibition. Furthermore, NMR data confirmed strain NIO-1008T produced salicylic acid (SA), which inhibited spore germination and mycelial growth. A greenhouse pot experiment showed that disease incidence significantly reduced to 70% in the presence of strain NIO-1008T, and 45.7% in SA, compared to control wheat plants. This study concludes A. enclensis NIO-1008T is a potential biocontrol candidate against F. oxysporum.
Keywords: F. oxysporum; Antifungal compound; Biocontrol activity; Marine bacteria; Salicylic acid